2022
DOI: 10.1088/1748-3190/ac91b9
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired materials to control and minimise insect attachment

Abstract: More than three quarters of all animal species on earth are insects, successfully inhabiting most ecosystems on the planet. Due to their opulence, insects provide the backbone of many biological processes, but also inflict adverse impacts on agricultural and stored products, buildings and human health. To countermeasure insect pests, the interactions of these animals with their surroundings have to be fully understood. This review focuses on the various forms of insect attachment, natural surfaces that have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 277 publications
0
4
0
Order By: Relevance
“…Adhesion on microrough surfaces has been a notorious problem for biological organisms, as smaller asperities introduce fine points that limit contact area. For organisms with fibrillar adhesives, such as geckos [31,32] or certain insects [33,34], this presents a relatively straightforward problem where the adhesive 'hairs' must be adapted to make proper contact on or in-between asperities. For organisms with soft adhesive pads (e.g.…”
Section: Materials Interactions For Sealingmentioning
confidence: 99%
“…Adhesion on microrough surfaces has been a notorious problem for biological organisms, as smaller asperities introduce fine points that limit contact area. For organisms with fibrillar adhesives, such as geckos [31,32] or certain insects [33,34], this presents a relatively straightforward problem where the adhesive 'hairs' must be adapted to make proper contact on or in-between asperities. For organisms with soft adhesive pads (e.g.…”
Section: Materials Interactions For Sealingmentioning
confidence: 99%
“…Historically, insects have provided a significant source for bioinspiration in engineered technologies [3][4][5][6] . The precise tuning of their sensory systems results from their physical anatomy and efficient encoding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…They are still the subject of intense research as technological solutions needed in a changing global society to control and minimize the ability of insects to attach to plants. 7…”
Section: Introductionmentioning
confidence: 99%
“…They are still the subject of intense research as technological solutions needed in a changing global society to control and minimize the ability of insects to attach to plants. 7 In this frame, recent studies have demonstrated that nanoparticles of kaolin, zeolite, and calcium carbonate can affect the attachment ability of the Southern green stinkbug Nezara viridula (Hemiptera: pentatomidae), one of the most relevant pentatomid insect pests in the world, 8 to natural and artificial surfaces. 9,10 It is to be emphasized that the ability to firmly adhere to the surface along the whole life cycle is of pivotal importance for insect survival and reproductive success.…”
Section: Introductionmentioning
confidence: 99%